Unruptured ovarian pregnancy following in-vitro fertilization: Missed diagnosis followed by successful laparoscopic management - S A Narvekar; P K VijayKumar; N Shetty; N Gupta; G B Ashwini; K A Rao (Wolters Kluwer Medknow Publications, 2008)
Ovarian pregnancy after in-vitro fertilization is rare and can be easily missed unless there is a high index of suspicion. Here we present such a case which was missed initially but was later successfully managed laparoscopically.